Dexmedetomidine Leads to the Mitigation of Myocardial Ischemia/Reperfusion-Induced Acute Lung Injury in Diabetic Rats Via Modulation of Hypoxia-Inducible Factor-1α - Chen,Siyu (2022)
ABSTRACT Introduction: The objective of this study is to investigate the protective mechanism of dexmedetomidine (Dex) in myocardial ischemia/reperfusion (MIR)-induced acute lung injury (ALI) of diabetic rats by inhibiting hypoxia-inducible factor-1α (HIF-1α). Methods: Initially, healthy male Sprague Dawley rats were treated with streptozocin to induce diabetes. Then, three weeks after the induction, Dex or lentiviral vector (LV)-HIF-1α was injected into the rats 30 minutes prior to the MIR modeling. After four weeks, lung tissues were harvested for pathological changes observation and the wet/dry weight (W/D) ratio determination. Afterwards, oxidative stress indicators and pro-inflammatory factors were measured. In addition, HIF-1α expression was assessed by immunohistochemistry and western blot analysis. Results: Dex could suppress inflammatory cell infiltration, improve lung tissue structure, reduce pathological score and the W/D ratio, and block oxidative stress and inflammatory response in MIR-induced ALI of diabetic rats. Besides, Dex could also inhibit HIF-1α expression. Moreover, Dex + LV-HIF-1α reversed the protective role of Dex on diabetic MIR-induced ALI. Conclusion: Our study has made it clear that Dex inhibited the upregulation of HIF-1α in diabetic MIR-induced ALI, and thus protect lung functions by quenching the accumulation of oxygen radical and reducing lung inflammatory response.